Reforming Road Management in Sub-Saharan Africa : Overcoming Obstacles to Implementation - Nyangaga, Francis N. (2012)
The obstacles to implementation of the entire package of reforms required by the Road Management Institute (RMI) are not only due to governments unwillingness to share management of resources and works with the private sector stakeholders. Of importance also is government uncertainty about: how the RMI concept may work in practice in Africa since no best practice examples are available from countries at similar levels of development. (New Zealand may be in a different league) how government may exercise its overall governance responsibilities by the ministry responsible for roads; and how to fund and manage the institutional reform process, including adequate capacity building at all levels as a solution to public sector redundancy problems. There is thus need for implementation plans that are more comprehensive than those available at this date, with strategies and budgets that clearly address the indicated obstacles and other relevant issues. The RMI- which has greatly contributed to the reform achievements so far-could also be a useful instrument to facilitate the drafting and implementation of such plans and, as a multi-donor supported initiative, help to coordinate donor support to the reform activities. This role, however, require strengthening of RMI's capacity and resources commensurate with the desired extent and level of activities, and perhaps a review of its current organization to ensure its effectiveness in relation to the character and focus of the mission.